I'd listen to my parents if they'd just shut up : what to say and not say when parenting teens today - Wolf, Anthony E. (Harper, 2011)
"Practical, dialogue-based advice for parents of teenagers from the author of the bestselling "Get out of My Life, But First Can You Drive Me and Cheryl to the Mall?" Anthony Wolf applies his philosophy and humor to a wide variety of everyday situations, showing both the way interactions tend to go (not so well) and why, then offers parents a script and guidance on how to achieve the most satisfying outcomes. Wolf deals with all the things that have dramatically changed in society to affect parenting in the 21st century, especially the role of the internet and electronic devices of all kinds in kids lives"--